UML Modeling and Black Box Testing Methods in the School Payment Information System - Ibnu Rasyid Munthe; Bhakti Helvi Rambe; Rahmadani Pane; Deci Irmayani; Marnis Nasution (Jurnal Mantik, 2020)
The payment information system enables the entry of cash transaction data to SMA Teluk Panji through administrative staff (TU). The TU maintains the money payment reports that the students pay. This approach is useful and allows students to know more about the money they have to spend. This approach gives students complete knowledge in paper form. Useful reports to discover how much they charged and students who did not pay. Model UML is a visual language for modeling and designing information systems or applications. As support for the development of this information system, UML uses diagrams and text. Any significant modeling influences the design of useful applications. The system must meet its specifications and be capable of converting data into usable and efficient users. The black box evaluation method serves as a software assessment. The method operates from inside the unknown. When the system testers test this system as designed and focused on the school payment information system, the information system software is appropriately controlled by the external control mechanism. The prototyping method aims to summarise the application developed during these phases.